(untitled) (Kinesiology, 2023)
Although previous studies have indicated the importance of a core strength and muscular endurance training in preadolescents and adolescents, there is a lack of evidence regarding effects of a long-term core training in unstable conditions. The purpose of this study was to compare the effects of core training in stable versus unstable body positions on core and upper body strength and muscular endurance in non-trained children aged 11-14 years. Participants were randomly assigned to either stable (SC, N=569) or unstable (UC, N=633) core-exercise group and assessed at baseline, after four, and eight months for sit-ups, dynamic trunk extension, static trunk extension, and push-ups. Repeated measures ANOVA, with time as a within factor, and exercise group, age, and gender as between factors, was employed for data analysis. Post-hoc comparisons showed greater absolute improvements after the eight-month training in UC compared to SC for all measures, age groups, and both genders (p≤.01), and greater relative improvements (differences in Cohen’s d between UC and SC ranged from 0.08 to 1.58), except for static trunk extension in 11- and 12-year-old participants. However, the differences between SC and UC in four-month effects were inconsistent. These results point out that core exercises in unstable compared to stable conditions have a greater capacity for long-term improvement of core and upper body strength and muscular endurance in non-trained preadolescents and adolescents. Key words: children, resistance training, abdominal strength, lower back strength